696. Mechanism of Cefiderocol high MIC mutants obtained in non-clinical FoR studies. (26th November 2018) - Ito, Akinobu; Nishikawa, Toru; Ishii, Ryuta; Kuroiwa, Miho; Ishioka, Yoshino; Kurihara, Naoko; Sakikawa, Ikue; Ota, Takeshi; Rokushima, Masatomo; Tsuji, Masakatsu; Sato, Takafumi; Yamano, Yoshinori
Abstract: Background: Cefiderocol (S-649266, CFDC) is a novel siderophore cephalosporin with activity against a wide variety of Gram-negative bacteria including carbapenem-resistant strains. We previously reported that CFDC is efficiently transported into Pseudomonas aeruginosa via iron transporter PiuA. In this study, we examined frequency of resistance of P. aeruginosa to CFDC, and investigated the resistance mechanisms of appeared colonies. Methods: Frequency of resistance (FoR) was determined by plating an overnight culture of P. aeruginosa PAO1 on Mueller–Hinton Agar containing 4× or 10×MIC of CFDC or ceftazidime (CAZ). Appeared colonies were analyzed by whole-genome sequencing (WGS) to identify genomic mutations. The mRNA expression was determined by real-time RT-PCR, and pyoverdine production was determined by MALDI-TOF/MS and expression of outer membrane protein was analyzed by SDS–PAGE and proteomic analysis. Results: The FoR to CFDC was 2.9 × 10 –8 and <7.1 × 10 –8, which were lower than those to CAZ (3.1 × 10 –7 and 3.4 × 10 –8 ) in the conditions of 4× and 10×MIC, respectively. MIC of CFDC against CFDC-derived mutant increased from 0.5 μg/mL (MIC against PAO1) to 2 μg/mL, and MICs of CAZ did not increase. In the case of CAZ-derived mutant, MICs of CAZ increased from 1 μg/mL (MIC against PAO1) to 16 μg/mL or higher, though MIC of CFDC did not increase, suggesting no cross-resistance between CFDC and CAZ. WGS identified mutations in upstream regions of pvdS ( pvdS mutant), which regulates pyoverdine synthesis, or fecI ( fecI mutant), which regulates the synthesis of iron transporter FecA contributing to the transport of iron citrate. The pvdS expression and pyoverdine production in the pvdS mutant were more than 4- and 6-fold higher than those in PAO1, respectively. The expression of fecA in the fecI mutant was more than ninefold higher than that in PAO1. Conclusion: The MIC increase of CFDC against P. aeruginosa occurred due to the mutation of iron transporter-related genes. The resistance acquisition risks should be low as the frequency of resistance to CFDC was lower and the MIC increase of CFDC against the mutants was smaller than that of CAZ. In addition, no cross-resistance between CFDC and CAZ was observed. Disclosures: A. Ito, Shionogi & Co., Ltd.: Employee, Salary. T. Nishikawa, Shionogi & Co., Ltd.: Employee, Salary. R. Ishii, Shionogi & Co., Ltd.: Employee, Salary. M. Kuroiwa, Shionogi & Co., Ltd.: Employee, Salary. Y. Ishioka, Shionogi & Co., Ltd.: Employee, Salary. N. Kurihara, Shionogi & Co., Ltd.: Employee, Salary. I. Sakikawa, Shionogi & Co., Ltd.: Employee, Salary. T. Ota, Shionogi & Co., Ltd.: Employee, Salary. M. Rokushima, Shionogi & Co., Ltd.: Employee, Salary. M. Tsuji, SHIONOGI & CO., LTD.: Employee, Salary. T. Sato, SHIONOGI & CO., LTD.: Employee, Salary. Y. Yamano, SHIONOGI & CO., LTD.: Employee, Salary.